Revealing and Mitigating Racial Bias and Discrimination in Financial Services - Scott, Maura L.; Bone, Sterling A.; Christensen, Glenn L.; Lederer, Anneliese; Mende, Martin; Christensen, Brandon G.; Cozac, Marina (Journal of Marketing Research, 2024)
Three field studies and a laboratory experiment reveal racial discrimination in financial loan services. The results show that (1) service employees provide Black (vs. White) customers with inferior service outcomes (i.e., products offered), (2) Black (vs. White) customers experience inferior service processes (employees’ warmth/competence), and (3) Black (vs. White) customers report lower loyalty intentions toward the firm. Such discrimination is not only morally wrong and illegal; it is also bad for business. Therefore, the authors also show when and why racial discrimination is mitigated: namely, when Black customers signal higher socioeconomic status, or a Black customer's company (for which they seek the loan) has a more complex and sophisticated legal structure (corporation vs. sole proprietorship). Exploring this mitigation effect further, the authors show that a more sophisticated business structure increases the employee's trust toward Black customers, which reduces the perceived default likelihood and increases the likelihood to offer a loan; yet, this process does not emerge for White applicants. The findings point to managerial and policy implications to mitigate racial discrimination.